Profile for male users treated in a reference center for sexually transmitted diseases - Adriano Rodrigues de Souza; Ana Paula Chaves de Freitas; Giselle Pereira Rovere; Ana Débora Assis Moura; Aline Rodrigues Feitoza (Rev Rene)
This study aims to trace the epidemiological profile of male patients with STD treated at a specialized center in STDs in the city of Fortaleza, CE, Brazil. In October 2008, the exploratory essay with quantitative approach, with 137 records of patients seen in 2007 was held. A form of research with clinical and socioeconomic data was used. It was found that 95.6% live in Fortaleza, 51% came through spontaneous demand, 49.6% were between 20 and 29 years of age, 46% reported having 10 or more years of study, the seafront appeared with the highest incidence of cases, 65% had one to five visits, while only 4% had used some medication, and 57.7% had genital warts as the primary diagnosis. It was concluded that the survey showed young men, mostly having finished high school, residents of poor neighborhoods.